Kepemimpinan dalam Persfektif Islam - Rahmat Ilyas (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This study aims to see the extent to which the concept of leadership in the Islamic perspective. This type of research is library research or library research. The data analysis method used is the Content Analysis method or what is called content analysis, which is a research method used to draw reflective and valid conclusions from data on the basis of context. The results of this study indicate that leadership can be defined as a process of influencing and directing employees in doing the work that has been assigned to them. In Islam there are several terms that refer to the notion of a leader. First, the word umara which is often referred to as ulul amri. The two leaders are often referred to as khadimul ummah (servants of the people), Third, the leader is often referred to as Imamah, and the fourth leader is often referred to as the caliph. The requirements for a leader in Islam are, Islam, baliq, intelligent, male, independent, knowledgeable, fair, have self-skills, have physical skills, have no ambition to get a position.